MRI Histogram Texture Feature Analysis of the Optic Nerve in the Patients with Optic Neuritis - Liu, Hong-Juan; Zhou, Huan-Fen; Zong, Lin-Xiong; Liu, Meng-Qi; Wei, Shi-Hui; Chen, Zhi-Ye (Chinese medical sciences journal, 2019)
Objective To evaluate the optic nerve impairment using MRI histogram texture analysis in the patients with optic neuritis.Methods The study included 60 patients with optic neuritis and 20 normal controls. The coronal T2 weighted imaging (T2WI) with fat saturation and enhanced T1 weighted imaging (T1WI) were performed to evaluate the optic nerve. MRI histogram texture features of the involved optic nerve were measured on the corresponding coronal T2WI images. The normal optic nerve (NON) was measured in the posterior 1/3 parts of the optic nerve. Kruskal-Wallis one-way ANOVA was used to compare the difference of texture features and receiver operating characteristic (ROC) curve were performed to evaluate the diagnostic value of texture features for the optic nerve impairment among the affected optic nerve with enhancement (ONwEN), affected optic nerve without enhancement (ONwoEN), contralateral normal appearing optic nerve (NAON) and NON.Results The histogram texture Energy and Entropy presented significant differences for ONwEN vs. ONwoEN (both P=0.000), ONwEN vs. NON (both P=0.000) and NAON vs. NON (both P<0.05). ROC analysis demonstrated that the area under the curve (AUC) of histogram texture Energy were 0.758, 0.795 and 0.701 for ONwEN vs. ONwoEN, ONwEN vs. NON and NAON vs. NON, AUC of Entropy were 0.758, 0.795 and 0.707 for ONwEN vs. ONwoEN, ONwEN vs. NON and NAON vs. NON.Conclusions The altered MRI histogram texture Energy and Entropy could be considered as a surrogate for MRI enhancement to evaluate the involved optic nerve and normal-appearing optic nerve in optic neuritis.